2021
DOI: 10.1101/2021.01.12.21249697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality of Diabetes-related Acute Metabolic Emergencies in COVID-19 patients: a systematic review and meta-analysis

Abstract: PurposeLittle is known on the mortality rate in COVID-19 related acute metabolic emergencies, namely diabetic ketoacidosis (DKA), hyperglycaemic hyperosmolar state (HHS), combined DKA/HHS, and euglycaemic diabetic ketoacidosis (EDKA).MethodsA systematic literature review was conducted using EMBASE, PubMed/Medline, and Google Scholar from January 1, 2020 to January 9, 2021 to identify all case report series, cross-sectional studies, and meta-analyses of case reports describing mortality rate in DKA, HHS, and ED… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…This has been confirmed in previous studies that immunosenescence and inflamm-aging may be an explanation (25,26). For the comorbidities, patients with chronic diseases, such as diabetes were more likely to show symptoms of Group 4, which has been confirmed (27). In addition, the results showed that for the imported cases and the clustered cases, the odds of symptoms of Group 2, Group 3, and Group 4 were all lower than indigenous cases or non-clustered cases, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…This has been confirmed in previous studies that immunosenescence and inflamm-aging may be an explanation (25,26). For the comorbidities, patients with chronic diseases, such as diabetes were more likely to show symptoms of Group 4, which has been confirmed (27). In addition, the results showed that for the imported cases and the clustered cases, the odds of symptoms of Group 2, Group 3, and Group 4 were all lower than indigenous cases or non-clustered cases, respectively.…”
Section: Discussionsupporting
confidence: 82%